Multiferroicity in manganite/titanate superlattices determined by oxygen pressure-mediated cation defects - Li, Z. (2013)
Increasing demand for spintronic devices, such as high-density memory elements, has generated interest in magnetoelectric coupling and multiferroic materials. In heteroepitaxial structures, magnetoelectric coupling occurs only near the strained interfaces, which is why the interface-rich multiferroic multilayer/superlattice is viewed as one of the most efficient ways to enhance the magnetoelectric coupling coefficient. However, both ferroelectric and ferromagnetic properties are difficult to be maintained when materials are shrunk to ultrathin layers, forming interfacial dead layers and limiting the application of these materials in atomic-scale devices. In this work, we demonstrate that the largely suppressed multiferroic properties of the La0.8Sr0.2MnO3 (16 unit cells)/BaTiO3 (12 unit cells) superlattice correlate with cation defects including both pure edge dislocations and planar defects. This conclusion is reached by combining atomic-resolution electron microscopy, piezoelectric force microscopy, and low-temperature magnetism measurements. Furthermore, it is shown that the density of the observed cation defects can be largely reduced by improving the oxygen off-stoichiometry through increasing oxygen pressure during growth, resulting in robust multiferroic properties. Only by eliminating oxygen vacancies during growth can the ferroic dead layers be further reduced. This work therefore opens the pathway for the integration of ferromagnetic and ferroelectric materials into magnetoelectric devices at diminished length scales.